Sex differences concerning the effects of ankle muscle fatigue on static postural control and spinal proprioceptive input at the ankle - Jo, Donguk; Bilodeau, Martin (Frontiers in Human Neuroscience, 2023)
Aims The main aim of this study was to determine sex differences in postural control changes with ankle muscle fatigue during a standing forward leaning (FL) task under different vision conditions. The secondary aim was to examine sex differences in the effect of fatigue on soleus (SOL) H-reflex amplitude, a measure of motoneuron excitability with activation of Ia afferents. Methods Fifteen healthy young adult males (mean age: 28.0 years) and 16 healthy young adult females (mean age: 26.1 years) were asked to perform four consecutive FL tasks [30 s; two with eyes open (EO) and two with eyes closed (EC)] before, and immediately following a fatiguing exercise consisting of alternating ankle plantarflexion (6 s) and dorsiflexion (2 s) maximal isometric contractions, and at 5 and 10 min of recovery. Center of pressure (COP) sway variables (mean position, standard deviation, ellipse area, average velocity, and frequency), an ankle co-contraction index, and a ratio of SOL H-reflex to the maximum amplitude of the compound muscle action potential (M-max) were obtained during the FL tasks. A rating of perceived fatigue (RPF) was also documented at the different time points. Results Time to task failure (reduction of 50% in maximal voluntary isometric contraction torque of ankle plantar flexors) and the increase in RPF value were not significantly different between males and females. Both sex groups showed similar and significant increases (p < 0.05) in mean COP sway velocity with no significant changes in co-contraction indices. No significant effects of fatigue and related interactions were found for SOL H/M-max ratio. Discussion The absence of a significant sex difference in postural control change (sway and co-contraction) with fatigue could be explained by similar perceived (RPF) and performance fatigability (exercise duration) between males and females in the present study. Fatigue did not lead to significant changes in SOL spinal motoneuron excitability with activation of Ia afferents.